A power-distribution joint optimization arrangement for multi-point source jamming system - Zhihao Cai; Shiqi Xing; Sinong Quan; Xinyuan Su; Junpeng Wang (Results in Engineering)
Increasing the jamming power while expanding the distribution area of the equivalent synthesis center increases the risk of the multi-point source jamming (MPSJ) system being detected by the monopulse radar. In order to achieve the optimal balance between the two, this paper proposes a power-distribution joint optimization arrangement for the MPSJ system. First, the geometric relationship distribution between the triplet antenna and the target is determined to derive the distribution law of the equivalent synthesis center of the triplet antenna. Second, a power-distribution joint optimization model based on jamming power and the area of the equivalent synthesis center distribution area is constructed by introducing the angle factor. Third, a multi-objective time-varying mapping particle swarm optimization (MOTPSO) algorithm is adopted to solve the model, thereby achieving the optimal arrangement. The experimental results show that when the jamming signal ratio is 13.87 dB, the equilateral triangle array can achieve the optimal balance between jamming power and the distribution area of the equivalent synthesis center. Comparative experiments show that the proposed method improves the uniformity of the solution set distribution by 40.84% on average and the computational efficiency by 85.02% on average.